The LAUsanne STAPHylococcus aureus ENdocarditis (LAUSTAPHEN) score: A prediction score to estimate initial risk for infective endocarditis in patients with S. aureus bacteremia - Papadimitriou-Olivgeris, Matthaios; Monney, Pierre; Mueller, Linda; Senn, Laurence; Guery, Benoit (Frontiers in Cardiovascular Medicine, 2022)
Infective endocarditis (IE) is a common complication of Staphylococcus aureus bacteraemia (SAB). The aim of the study was to develop and validate a prediction score to determine IE risk among SAB. This retrospective study included adults with SAB (2015-21) and divided them in a derivation and a validation cohort. Using the modified 2015 European Society of Cardiology modified Duke Criteria for definite IE, the LAUSTAPHEN score was compared to previous scores. Among 821 SAB episodes, 419 and 402 were divided in derivation and validation cohorts, respectively. Transthoracic and transoesophageal echocardiography (TOE) were performed in 77.5% and 42.1% of episodes, respectively. Definite IE was diagnosed in 118 episodes (14.4%). Derivation cohort established that cardiac predisposing factors, cardiac implantable electronic devices, prolonged bacteraemia ≥48h and vascular phenomena were independently associated with IE. In addition to those parameters, native bone and joint infection were used to constitute the LAUSTAPHEN score. LAUSTAPHEN and VIRSTA scores misclassified <4% of IE cases as low-risk. Misclassification using POSITIVE and PREDICT scores was >10%. The number of TOEs required to safely exclude IE would have been 66.9% and 51.6% with VIRSTA and LAUSTAPHEN, respectively. LAUSTAPHEN and VIRSTA scores exhibited the lowest misclassification rate of IE cases to the low-risk group. However, the number of patients requiring TOE was higher for VIRSTA than for LAUSTAPHEN.